Acquisition of triploid germplasms by controlled hybridisation between diploid and tetraploid in Chinese jujube. Issue 1 (2nd January 2019) - Yan, Fenfen; Wang, Lihu; Zheng, Xingjuan; Luo, Zhi; Wang, Jiurui; Liu, Mengjun
ABSTRACT: 'Chenguang' is the first released tetraploid cultivar (2n = 4x = 48) of Chinese jujube ( Ziziphus jujuba Mill.) induced by colchicine. The purpose of this study was to create triploid germplasms by using 'Chenguang' as a parent. The controlled crosses between autotetraploid 'Chenguang' and diploid 'Dongzao' were carried out from 2013 to 2015 by maintaining the 2 parents in a nylon net and employing bees as pollinator. A total of 606 fruits were produced, yet only 17 seeds were obtained from 'Dongzao' and none from 'Chenguang'. Direct sowing of the seeds in greenhouse showed a higher seedling rate than embryo culture. Four progeny plants were eventually obtained in the greenhouse and all of them were confirmed as authentic hybrids by SSR marker technique. At last, 3 triploids and 1 diploid were identified by flow cytometric analysis. Consequently, tetraploid 'Chenguang' with high pollen vitality and pollen number per anther could be used as a reliable 2n pollen provider, and the 2x × 4x cross combination type is more suitable for triploid creation in Chinese jujube. This is the first successful production of triploid hybrids by controlled cross between diploids and tetraploids in jujube.